2015
DOI: 10.4103/1995-705x.172197
|View full text |Cite
|
Sign up to set email alerts
|

Right bundle branch block and electromechanical coupling of the right ventricle: An echocardiographic study

Abstract: Background:A growing body of evidence suggests that the presence of a right bundle branch block (RBBB) is a negative prognostic indicator in patients with and without preexisting heart disease. Even though electromechanical activation of the right ventricle (RV) in patients with RBBB and pulmonary hypertension (PH) has been investigated; a direct comparison of the presence of RBBB, on the duration of RV mechanical systole using echocardiography has not been studied.Materials and Methods:In this retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Although TAPSE was not statistically significant in patients with RBBB, we observed decrease in RBBB than normal individuals. Similar to our results Miller et al (14) demonstrated that RBBB leads to a measurable prolongation of TAPSE in patients without pulmonary hypertension (PH), however it was statistically insignificant (P >0.05). Time-to-peak of TAPSE was not significantly prolonged in patients with PH.…”
Section: Discussionsupporting
confidence: 92%
“…Although TAPSE was not statistically significant in patients with RBBB, we observed decrease in RBBB than normal individuals. Similar to our results Miller et al (14) demonstrated that RBBB leads to a measurable prolongation of TAPSE in patients without pulmonary hypertension (PH), however it was statistically insignificant (P >0.05). Time-to-peak of TAPSE was not significantly prolonged in patients with PH.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, multiple logistic regression test was performed to determine predictors of abnormal diastolic function. Intra- and inter-observer variability in our echo lab for this patient population has been previously reported [ 25 , 26 ]. A P-value of less than 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 95%
“…One possible pathophysiological mechanism for our discovery is that RBBB is more susceptible to dys-synchronized ventricular contractions, resulting in progressive decreased ventricular filling, than LBBB, which in turn leads to an increased risk of developing MACCEs ( Figueroa-Triana et al, 2021 ). Thus, compared to patients with LBBB, this might explain why a new permanent RBBB patient seems more susceptible to ischemic cardiomyopathy ( Miller et al, 2015 ) and at a higher risk for MACCEs and all-cause mortality. In addition, we found that patients with BBB were more likely to have higher levels of triglyceride, while patients with LBBB were more likely to have higher levels of LDL-C and apolipoprotein B.…”
Section: Discussionmentioning
confidence: 99%